2019
DOI: 10.3390/ijms20051174
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Chemerin Levels, but not the RARRES2 Polymorphisms, Predict the Long-Term Outcome of Angiographically Confirmed Coronary Artery Disease

Abstract: Chemerin, a novel adipokine, has been associated with metabolic, inflammatory, and atherosclerotic diseases. We aimed to determine the genetic basis of chemerin levels by conducting a genome-wide association study (GWAS) and to investigate the role of RARRES2 polymorphisms and circulating chemerin levels in the long-term outcome of coronary artery disease (CAD). A total of 2197 participants from the Taiwan Biobank (TWB) were recruited for the GWAS analysis, and 481 patients with angiographically confirmed CAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 40 publications
4
24
0
Order By: Relevance
“…This increase, with the positive correlation between hs-CRP and chemerin in hypertensive group may point to the fact that some sort of inflammation may influence the role of chemerin with hypertension. Some studies confirmed the association of circulating chemerin with hs-CRP and hypertension (ZYLLA et al, 2017;ER et al, 2019). In agreement with the present study, the researchers found that hs-CRP increased in hypertensive patients and its high levels were considered a predictor of hypertension development in prehypertensives and normotensives (SESSO et al, 2003;BAUTISTA et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…This increase, with the positive correlation between hs-CRP and chemerin in hypertensive group may point to the fact that some sort of inflammation may influence the role of chemerin with hypertension. Some studies confirmed the association of circulating chemerin with hs-CRP and hypertension (ZYLLA et al, 2017;ER et al, 2019). In agreement with the present study, the researchers found that hs-CRP increased in hypertensive patients and its high levels were considered a predictor of hypertension development in prehypertensives and normotensives (SESSO et al, 2003;BAUTISTA et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, a 4-week infusion of chemerin-9, an agonist of CMKLR1, induces a decrease in aortic atherosclerotic lesions in apolipoprotein E-deficient (ApoE -/-) mice [ 86 ], while in another study using the same animal model, the contrary effect was reported, showing that chemerin protein levels correlated with inflammatory markers and plaque formation [ 138 ]. In the same line, although the majority of studies suggest that chemerin circulating levels are associated with the presence and severity of atherosclerosis [ 127 , 129 , 130 , 132 , 139 , 140 , 141 , 142 ], there are also contradictory results [ 124 , 143 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…We analysed the association of chemerin level with multiple phenotypes, circulating inflammatory markers and adipokines in two studies that enrolled a relatively small number of participants with pre-existing CAD in Taiwan. 11,25 In order to fully understand the role of chemerin in human health and exclude the bias arising from the effect of medications in different ethnicities, studies with a large number of healthy participants are needed.…”
Section: Introductionmentioning
confidence: 99%